Occurrence and genetic characteristics of mcr-1-positive colistin-resistant E. coli from poultry environments in Bangladesh. (September 2020) - Amin, Mohammed Badrul; Sraboni, Ajrin Sultana; Hossain, Muhammed Iqbal; Roy, Subarna; Mozmader, TIM Amin Uddin; Unicomb, Leanne; Rousham, Emily K.; Islam, Mohammad Aminul
Highlights: Circa 94% extended-spectrum β-lactamase (ESBL)-producing Escherichia coli from poultry sources are colistin resistant and 13.5% colistin-resistant E. coli are positive for the mcr -1 gene. The mcr -1-positive isolates are resistant to many antibiotics that are critical for human health. Resistance to other antibiotics including third-generation cephalosporin, aminoglycoside and fluoroquinolone is carried by the mcr -1 plasmid. This is the first report on occurrence of plasmid-mediated mcr -1-producing E. coli from poultry sources in Bangladesh. Abstract: Objectives: Colistin is one of the last-resort antibiotics for the treatment of multidrug-resistant (MDR) Gram-negative bacterial infections. We determined the occurrence and characteristics of mcr- 1-producing Escherichia coli obtained from live bird markets (LBMs), rural poultry farms (RPFs) and rural household backyard poultry environments (HBPs) in Bangladesh. Methods: We tested 104 extended-spectrum β-lactamase (ESBL)-producing E. coli isolated during 2017–2018 from poultry sources for colistin resistance. We analysed the resistant isolates for the mcr genes and characterized mcr -positive isolates for antibiotic susceptibility, antibiotic resistance genes, transmissible plasmids and clonal diversity. Results: Of 104 isolates, 98 (94%) had MICcolistin ≥4 μg/mL and 14 (13.5%) were positive for mcr- 1, of which 10 were from LBMs ( n = 10), 3 were from RPFs and 1 was from an HBP. All 14 mcr- 1 E. coli were resistant to third-generation cephalosporin and tetracycline, whereas 12 were resistant to fluoroquinolone and sulfamethoxazole, 10 were resistant to aminoglycosides and 3 were resistant to nitrofurantoin. Four isolates carried conjugative mcr- 1 plasmid of 23–55 MDa in size. The 55 MDa plasmid found in two isolates carried additional resistant genes including bla CTX-M-group-1 and bla TEM-1 (ESBL), qnrB (fluoroquinolone), and rmtB (aminoglycoside). These plasmids belong to the IncF family with additional replicons: HI1 and N. Enterobacterial repetitive intergenic consensus-polymerase chain reaction revealed a heterogeneous banding pattern of mcr- 1-positive isolates. Conclusion: We report a 13.5% prevalence of mcr- 1-positive MDR E. coli in poultry faecal samples predominantly from LBMs in Bangladesh accentuating the need for safe disposal of poultry faeces and hygiene practices among people exposed to poultry.